A Wireless Sensor Network System with a Jumping Node for Unfriendly Environments - Jun Zhang; Guangming Song; Guifang Qiao; Zhen Li; Aimin Wang (International Journal of Distributed Sensor Networks)
Mobile robots have been adopted to repair failed wireless sensor network systems for node damage, battery exhaustion, or obstacles. But most of the robots use wheeled locomotion manner, which does not work well or even fails when confronted with obstacles in uneven terrains. To solve this problem, this paper presents the design of a jumping robot to serve as a robotic node for wireless sensor networks. The robot can jump up to or over obstacles to repair the broken network connections. The robot senses its posture angle by using an acceleration sensor and self-rights automatically by using a pole leg after falling down on the ground. The robot also can steer and adjust its take-off angle by the pole leg. A network monitoring system with the proposed robot is built to test its basic locomotion capabilities and the network repair function. Experimental results show that the robot can jump about 90 cm in height and traverse 50 cm far at a take-off angle of 75 degrees. The robot can repair the network by jumping up to a 10 cm high platform. The proposed system with a jumping node can provide powerful support for applications in unfriendly environments.